HIV medical care interruption among people living with HIV in Spain, 2004 - 2020 - Izquierdo, Rebeca; Rava, Marta; Moreno-García, Estela; Blanco, José Ramón; Asensi, Víctor; Cervero, Miguel; Curran, Adrián; Rubio, Rafael; Iribarren, José Antonio; Jarrín, Inmaculada (Wolters Kluwer, 2023)
Objective: We estimated the incidence rate of HIV medical care interruption (MCI) and its evolution over a 16-year-period, and identified associated risk factors among HIV-positive individuals from the Cohort of the Spanish AIDS Research Network in 2004¿2020. Design: We included antiretroviral-naive individuals aged at least 18 years at enrolment, recruited between January 1, 2004, and August 30, 2019, and followed-up until November 30, 2020. Methods: Individuals with any time interval of at least 15 months between two visits were defined as having a MCI. We calculated the incidence rate (IR) of having at least one MCI and used multivariable Poisson regression models to identify associated risk factors. Results: Of 15 274 individuals, 5481 (35.9%) had at least one MCI. Of those, 2536 (46.3%) returned to HIV care after MCI and 3753 (68.5%) were lost to follow-up at the end of the study period. The incidence rate (IR) of MCI was 7.2/100 person-years (py) [95% confidence interval (CI): 7.0¿7.4]. The annual IR gradually decreased from 20.5/100 py (95% CI: 16.4¿25.6) in 2004 to 4.9/100 py (95% CI: 4.4¿5.5) in 2014, a slight increase was observed between 2015 and 2018, reaching 9.3/100 py (95% CI: 8.6¿10.2) in 2019. Risk factors for MCI included younger age, lower educational level, having contracted HIV infection through injecting drug use or heterosexual intercourse, having been born outside of Spain, and CD4+ cell count >200 cell/¿l, viral load <100 000 and co-infection with hepatitis C virus at enrolment. Conclusions: Around a third of individuals had at least one MCI during the follow-up. Identified predictors of MCI can help health workers to target and support most vulnerable individuals.